2009
DOI: 10.1148/radiol.2512081829
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Carotid Plaque Neovascularization Detected by Using Contrast-enhanced US with Clinical Symptoms

Abstract: Symptomatic patients had more intense contrast agent enhancement in the plaque than asymptomatic patients, suggesting that contrast-enhanced carotid US may be used for plaque risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
2
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 27 publications
6
116
2
8
Order By: Relevance
“…Further, a different pattern of plaque vascularization was observed in the acute symptomatic patients, represented by a major and more diffuse contrast enhancement, completely different from the pattern of the majority of the asymptomatic plaques. These data have been confirmed by other Authors (Xiong, 2009;, Chowdhury ,2010, Cosgrove, 2009). Histological specimens with immunostaining obtained from CEA confirmed a relevant angiogenesis in symptomatic plaques when compared to asymptomatic ones.…”
Section: Contrast Ultrasound Findingssupporting
confidence: 86%
“…Further, a different pattern of plaque vascularization was observed in the acute symptomatic patients, represented by a major and more diffuse contrast enhancement, completely different from the pattern of the majority of the asymptomatic plaques. These data have been confirmed by other Authors (Xiong, 2009;, Chowdhury ,2010, Cosgrove, 2009). Histological specimens with immunostaining obtained from CEA confirmed a relevant angiogenesis in symptomatic plaques when compared to asymptomatic ones.…”
Section: Contrast Ultrasound Findingssupporting
confidence: 86%
“…Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45]. Furthermore, wholly consistent with the concept that more vulner- able plaque contains a higher degree of neovascularization, recent retrospective studies revealed the association between plaque enhancement on contrast-enhanced ultrasound imaging and clinical symptoms including cerebrovascular events in patients with carotid atherosclerosis [19,46,47]. Therefore, contrast-enhanced ultrasound examination of the carotid artery may provide a novel, noninvasive clinical tool to identify and quantify the presence and the extent of arterial plaque neovascularization in patients at risk for developing symptomatic atherosclerosis, thus permitting more reliable assessment of cardiovascular risk.…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Imsupporting
confidence: 59%
“…50,91 Studies comparing plaque enhancement in asymptomatic and symptomatic plaques have demonstrated that plaque enhancement is markedly increased in patients with symptomatic plaque and is associated with a higher rate of cardiovascular events in general. 102,122,130 Retention of microbubbles on the plaque surface on delayed images has been shown to correlate with plaque disruption and inflammation as macrophages are known to phagocytose this contrast agent. 56 When combined with B-mode ultrasonography, CEUS provides further details in plaque characterization.…”
Section: Ceusmentioning
confidence: 99%